INDIVIDUALIZING EDUCATION: PSYCHOLOGICAL PRINCIPLES FOR PERSONALIZED LEARNING (American Journal of Interdisciplinary Research and Development, 2024)
Effective education must address the unique needs, abilities, and learning preferences of each student. This article explores the psychological foundations that underpin an individualized approach to education. Drawing on theories of cognitive development, motivation, and individual differences, the paper outlines key principles for designing and implementing personalized learning experiences. The discussed principles include adapting instruction to students' readiness levels, fostering autonomy and intrinsic motivation, and leveraging individual strengths. The article also examines the practical application of these principles in various educational contexts, as well as the empirical evidence supporting the efficacy of an individualized approach. Implications for educational policy, teacher training, and future research are discussed.